2009
DOI: 10.1007/s00464-009-0383-9
|View full text |Cite
|
Sign up to set email alerts
|

Injuries caused by Veress needle insertion for creation of pneumoperitoneum: a systematic literature review

Abstract: The insertion of the Veress needle in the abdominal midline, at the umbilicus, poses serious risk to the life of patients. Therefore, further studies should be conducted to investigate alternative sites for Veress needle insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
1
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 26 publications
1
74
1
8
Order By: Relevance
“…It is less than 0.2% in the case of diagnostic laparoscopy [5,8], but more frequent in operative laparoscopy (up to 8% in laparoscopic-assisted vaginal hysterectomy) and frequently caused by sharp electrosurgical dissection [5,8]. Jelovsek et al [9] concluded that the overall incidence of injury to the lower urinary tract in 126 consecutive total laparoscopic hysterectomies was 4.0%, but Lafay Pillet et al [10] had a rate of bladder injuries of 1% in 1,501 procedures, decreasing with the surgeon experience and others report even less [11]. Although the majority of bladder injuries are detected at the time of surgery, either directly by the surgeon seeing urinary spilling or by the anaesthetist noticing gas or blood in the urine bag [7,12], Jelovsek et al [9] recommended the performance of cystoscopy with intravenous indigo-carmine dye at the time of total laparoscopic hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is less than 0.2% in the case of diagnostic laparoscopy [5,8], but more frequent in operative laparoscopy (up to 8% in laparoscopic-assisted vaginal hysterectomy) and frequently caused by sharp electrosurgical dissection [5,8]. Jelovsek et al [9] concluded that the overall incidence of injury to the lower urinary tract in 126 consecutive total laparoscopic hysterectomies was 4.0%, but Lafay Pillet et al [10] had a rate of bladder injuries of 1% in 1,501 procedures, decreasing with the surgeon experience and others report even less [11]. Although the majority of bladder injuries are detected at the time of surgery, either directly by the surgeon seeing urinary spilling or by the anaesthetist noticing gas or blood in the urine bag [7,12], Jelovsek et al [9] recommended the performance of cystoscopy with intravenous indigo-carmine dye at the time of total laparoscopic hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Many surgeons have surpassed the learning curve for most procedures and therefore mayor complications have been reduced significantly. Azevedo et al [15] in a cohort of in 696,502 patients who underwent a laparoscopic procedure using the closed technique (Veress needle) to enter the abdominal cavity have reported an incidence rate of vascular and visceral injuries of 0.018% and of 0.0024%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is due largely to successful personal experiences and the fact that the open technique has been linked to some technical difficulties such as increased time to access the peritoneal cavity compared to the closed technique and gas leakage through incision. [13][14][15][16][17][18] In a meta-analysis by Bonjer et al [19] vascular injuries occurred in 0.083% of patients using the closed technique and in 0.075% of patients using the open technique, while visceral injuries occurred in 0.048% of patients using the closed technique and in 0.0% using the open technique. The meta-analysis showed a tendency to eliminate visceral injuries and reduce the risk of major complications with the open technique.…”
Section: Discussionmentioning
confidence: 99%
“…The abdominal aorta and vena cava, as well as the common iliac vessels, are particularly prone to injury during Veress needle puncture in the vicinity of the umbilical scar 10 . Despite the low prevalence of this occurrence (0.05% to 0.5%), mortality rates range between 8% and 17%, reaching 21% when there is unnoticed associated intestinal lesions [4][5][6][7][8][9][10][11] . The severity of this type of iatrogenic injury is minimized when the punctures are made in locations away from the midline 12 15 .…”
Section: Original Articlementioning
confidence: 99%